2014
DOI: 10.1371/journal.pone.0088539
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Fatty Acid Profile Underlies the Reduced Inflammatory State of Metabolically Healthy Obese Individuals

Abstract: BackgroundObesity is associated with numerous health complications; however, a subgroup of obese individuals (termed the metabolically healthy obese or MHO) appear to have lower risk for complications such as type 2 diabetes and cardiovascular disease. Emerging evidence suggests that MHO individuals have reduced inflammation compared to their metabolically unhealthy obese (MUO) counterparts. As it is recognized that fatty acids (FAs) have a strong relationship with inflammation, the current study aimed to unco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 49 publications
5
80
1
Order By: Relevance
“…These studies have consistently shown elevated levels of C14:0 (myristic acid) in adults as well [13,32,33]. A study on lean, healthy, metabolically healthy, and metabolically unhealthy obese adults showed that C14:0 even has a dose-response relationship with the status of obesity and according to the degree of obesity-related inflammation [33]. Whether this would show up also in children with different degrees of obesity or explicitly for LPCaC14:0 is an open question.…”
Section: Discussionmentioning
confidence: 98%
“…These studies have consistently shown elevated levels of C14:0 (myristic acid) in adults as well [13,32,33]. A study on lean, healthy, metabolically healthy, and metabolically unhealthy obese adults showed that C14:0 even has a dose-response relationship with the status of obesity and according to the degree of obesity-related inflammation [33]. Whether this would show up also in children with different degrees of obesity or explicitly for LPCaC14:0 is an open question.…”
Section: Discussionmentioning
confidence: 98%
“…The importance of unsaturated fatty acids in mediating inflammation is enhanced by a recent study showing a distinct fatty acid profile between MHO and unhealthy obese individuals, specifically for saturated fatty acids [64]. Further comparisons of these two groups are required to better identify potential mechanisms of protection against obesity-related insulin resistance and inflammation and to develop preventive and therapeutic strategies.…”
Section: Page 11 Of 24mentioning
confidence: 99%
“…Taken together, these findings suggest that a fat-enriched diet is central to the loss of epithelial barrier integrity, which in turn directly or indirectly affects the microbiota, causing a dysbiosis that further alters epithelial homeostasis. Several studies have addressed the long-term effects of HF diet in such pathologies (40)(41)(42). Interestingly, most studies have characterized the fecal or cecal luminal microbiota; however, very few have attempted to characterize the mucosa-associated microbiota in the upper digestive segments, even though basic functions performed by the SI need to be tightly preserved to maintain health.…”
Section: Significancementioning
confidence: 99%